Síntese e caracterização de alvo de óxido de zinco dopado com alumínio - Melo, Emanuel Benedito de [UNESP] (2015)
This thesis had intended to perform the synthesis and characterization of aluminum-doped zinc oxide (AZO) for making ceramic targets for use in conductive thin film deposition (TCO) by sputtering technique. The aluminium-doped zinc oxide was obtained by Pechini Method. The structuring of the material, through its precursor, by heat treatment in air. The characterization of the material obtained was performed by Simultaneous Thermal Analysis techniques (TG, DTG, DTA), X-Ray Diffraction (XRD), Structural Refinement by the Rietveld method (REMR), scanning electron microscopy (EDS) and Semi-quantitative Analysis by X-Ray Energy (MEV). The results showed that the ~600ºC, the material in the form of nanostructured powder, had the majority of organic disposal of precursors as indicated by thermal analysis TG, DTG, DTA. Around this temperature can be noted, too, the beginning of the structure of the crystalline phase confirmed by X-Ray Diffraction Analysis. Finally, above 1000ºC treatments allowed the obtaining of oxides with high crystallinity, absence of resistive phases, in addition to the complete elimination of organics. Up to 1200ºC aluminum concentration increased due to volatilization of zinc. The target was made from a powder suspension of AZO in ethyleneglycol that was deposited in demarcation for mask over alumina getting disk heat treatment for sintering of grain. This target was used for the synthesis of thin films on glass substrates by Cathodic spraying technique. With the target, it was possible to accomplish the thin film deposition of type TCO. The thin films were characterization by optical transmittance measurements in the visible spectrum, DRX, and electrical conductivity test. The results of characterization showed that the ceramic target, obtained by Pechini Method, made possible the growth of thin films with low electrical resistitivity with values near the 1.10-3 cm, plus a high transmittance (90%) characterized as...